Internet from space: How new satellite connections could affect global internet governance - Daniel Voelsen (Stiftung Wissenschaft und Politik (SWP), 2021)
A number of companies from the US and China plan to build networks of several thousand satellites each to enable access to the Internet from any point on Earth. These satellites will be stationed in low Earth orbit. If these plans are put into practice, the global Internet infrastructure will acquire a whole new dimension. This would have far-reaching consequences for Internet access, the security and resilience of Internet infrastructure, and power relations in global Internet governance. The home countries of the leading companies - above all the US, followed by China - would have extensive potential for political influence. They would be able to control, at the level of the Internet's global infrastructure, the worldwide flows of information. This research paper draws two scenarios to illustrate the range of possible developments and the corresponding potential responses: one describes the development of global oligopolies, the other a form of politically regulated global competition. German and European political decision-makers should use regulations and public funding to work towards a future Internet infrastructure that is secure and reliable. The basis for this is the redundancy and diversity of the underlying technology. To this end, the new satellite constellations can be an important part of an appropriate mix of technologies. It would be both politically and economically desirable for Europe to build its own constellation.
Keywords: 320; Infrastrukturelle Erschließung; Ziele und Programme internationalen Akteurs; Zugang zu Dienstleistungen; Status und Rolle im internationalen System; Privatwirtschaft; Staat; Strategische Überlegenheit; Multilateralismus; Wirkung/Auswirkung; Internationaler Informationsaustausch; Kommunikation in den internationalen Beziehungen; Entwicklungsperspektive und -tendenz